2020
DOI: 10.1101/2020.03.27.011908
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pyocin efficacy in a murine model ofPseudomonas aeruginosasepsis

Abstract: Synopsis BackgroundBloodstream infections with antibiotic resistant Pseudomonas aeruginosa are common and increasingly difficult to treat. Pyocins are naturally occurring protein antibiotics produced by P. aeruginosa that have potential for human use. ObjectivesTo determine if pyocin treatment is effective in a murine model of sepsis with P. aeruginosa. MethodsRecombinant pyocins S5 and AP41 were purified tested for efficacy in a Galleria mellonella infection model and a murine model of P. aeruginosa sepsis. R… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
(29 reference statements)
0
5
0
Order By: Relevance
“…Colicin and bacteriophage intoxication: Colicins and bacteriophages typically associate with two components of the OM to activate import and infection, respectively, in E. coli . The long tail fibers of bacteriophage T4 bind LPS and OmpC ( 62 ), and colicin E9 binds OmpF and BtuB ( 35 , 42 ). In both cases, the two components are colocated by virtue of the lipid-mediated OMP network.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Colicin and bacteriophage intoxication: Colicins and bacteriophages typically associate with two components of the OM to activate import and infection, respectively, in E. coli . The long tail fibers of bacteriophage T4 bind LPS and OmpC ( 62 ), and colicin E9 binds OmpF and BtuB ( 35 , 42 ). In both cases, the two components are colocated by virtue of the lipid-mediated OMP network.…”
Section: Discussionmentioning
confidence: 99%
“…We first established the relative cellular distribution of our target OMPs using fluorescence imaging in E. coli MG1655 cells. OmpF, FepA, and BtuB were specifically labeled with fluorescently tagged, high-affinity colicins inactivated for toxicity (27,(33)(34)(35) and visualized by total internal reflection fluorescence microscopy (fig. S1, A and B).…”
Section: Strategy For Capturing Omp Near-neighbor Contacts In Live E ...mentioning
confidence: 99%
“…A recent study showed that colicins can be used to disrupt biofilm integrity [223]. Moreover, when injected into the bloodstream of mice, pyocin S5 was observed to retain its functionality and to improve mouse survival to Pseudomonas infections [224]. Another study demonstrated that microcapsule delivery of the active form of colicin Ia reduced E. coli colonisation in murine models [225].…”
Section: Discussionmentioning
confidence: 99%
“…Narrow-spectrum protein bacteriocins are emerging as promising alternative antibiotics and could be utilized to target specific pathogenic bacteria in the complex microbial community of the human microbiota, sparing the key eubiotic organisms ( Brown et al, 2015 ; McCaughey et al, 2016 ; Six et al, 2020 ). The best studied of the protein bacteriocins are the colicins, which specifically target E. coli and strains of other closely related bacterial species ( Cascales et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%